2022
DOI: 10.1002/anie.202206916
|View full text |Cite
|
Sign up to set email alerts
|

Mesityl‐Functionalized Multi‐Resonance Organoboron Delayed Fluorescent Frameworks with Wide‐Range Color Tunability for Narrowband OLEDs

Abstract: Polycyclo‐heteraborin multi‐resonance (MR) emitters are promising for high color‐purity organic light‐emitting diodes (OLEDs). Here, unlike the most common heteroatom ternary‐doped (X/B/N) frameworks, a binary‐doped (B/N) skeleton is reported with a large energy band for wide‐range color tunability. Based on this parent‐segment, a “one‐pot” catalyst‐free borylation method is developed which generates deep blue to pure green MR emitters from readily available starting materials, with peaks at 426–532 nm and ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 55 publications
0
34
0
Order By: Relevance
“…The HF OLED based on BN2 shows strong green light with an EL peak at 540 nm (CIE x,y = 0.32, 0.64; FWHM = 41 nm) and a maximum luminance as high as 33930 cd m ‒2 . Impressive η C , η P and η ext of 158.8 cd A ‒1 , 136.8 lm W ‒1 and 37.6% are achieved, being the highest EL efficiencies for green MR-TADF materials 54 , 55 .…”
Section: Resultsmentioning
confidence: 96%
“…The HF OLED based on BN2 shows strong green light with an EL peak at 540 nm (CIE x,y = 0.32, 0.64; FWHM = 41 nm) and a maximum luminance as high as 33930 cd m ‒2 . Impressive η C , η P and η ext of 158.8 cd A ‒1 , 136.8 lm W ‒1 and 37.6% are achieved, being the highest EL efficiencies for green MR-TADF materials 54 , 55 .…”
Section: Resultsmentioning
confidence: 96%
“…In order to achieve high-color purity deep-blue emission, narrowband chromophores with electroluminescent (EL) emission peaks at 460 ± 5 nm are required. At the same emission peak, the narrower FWHM manifests a smaller CIE y value (and a higher current efficiency/CIE y index) and relatively lower excited state (S 1 ) energies due to the bathochromic shift for the spectral onset. However, owing to the difficulty in managing large bandgap chromophores and maintaining efficient radiative emissions, molecular design strategies for color-saturated deep-blue and high photoluminescence quantum yield (PLQY) emitters are still rare and challenging. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, Duan et al reported a B,N-doped pentacene emitter, mDBIC, that emits in the deep blue (lPL = 426 nm, FWHM = 26 nm) region in 2 wt% doped mCP film and was used as the terminal emitter in a HF device that showed excellent performance at the deep blue color point (lEL = 431 nm, FWHM = 42 nm, EQEmax = 13.5%, CIEy = 0.05). 21 Pushing the emission further into the deep blue in MR-TADF compounds remains exceedingly difficult. The B,N-doped heptacene system α-3BNOH (lPL = 390 nm, ΔEST = 0.30 eV, τd = 0.45 μs, THF) 22 that we previously reported represents a rare example of a MR-TADF purple emitter as does the B,O-doped triangulene emitter, DOBNA (lPL = 398 nm, ΔEST = 0.18 eV, τd = 66 μs, 1wt% in PMMA).…”
Section: Introductionmentioning
confidence: 99%